A Portal Adoption Program to Enhance Patient Satisfaction in Primary Care. Issue 8 (August 2020) - Crockett, Shelli; Carter-Templeton, Heather
Abstract : Patient engagement technologies have become a focal point for defining quality in government and medical practice arenas. Patient portals are recognized as a promising mechanism to foster patient engagement and, as such, have become embedded in major healthcare reform initiatives. Despite sweeping implementation endeavors, portal adoption rates among patients remain low and create a significant gap in quality-based reimbursement. The purpose of this research was to evaluate a 12-week portal adoption program in the primary care setting featuring customized tablets with a patient-centric design for targeted point-of-contact portal registration. This project focused on three objectives: (1) achieve a 75% metric for portal adoption to align with highest tier adopters; (2) evaluate patient satisfaction for measuring perceived ease-of-use and usefulness of system; and (3) assess cost-effectiveness in determining sustainability and potential to replicate the initiative throughout other primary care settings. An outcome evaluation of the program revealed a 90% portal utilization rate, 94% new patient portal adoption rate, and 79% existing patient portal adoption rate during the data collection period. A χ 2 analysis revealed a statistically significant difference in patient satisfaction scoring relative to efficiency, quality of care, and safety of information based on sex and insurance carrier demographics.